2003
DOI: 10.1108/02651330310485153
|View full text |Cite
|
Sign up to set email alerts
|

Does culture explain acceptance of new products in a country?

Abstract: This paper investigates the role of cultural differences in the acceptance of new products, as moderated by socio-economic variables. In order to assess the relationship, an analysis utilizing Hofstede's cultural dimensions, along with secondary data representing socio-economic structure and the penetration rate of new products was undertaken. The results demonstrate that power distance and uncertainty avoidance hinder the acceptance of new products. Also found is that individualism has a positive effect but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
242
2
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(275 citation statements)
references
References 55 publications
10
242
2
11
Order By: Relevance
“…Major changes in climate and ecology, historical events, population migration, or cultural diffusion may slowly affect culture (Triandis 1995). However, national cultures are generally thought to be stable over time , Hofstede 2001, Yeniyurt and Townsend 2003. Cross-cultural researchers have documented various dimensions of national culture.…”
Section: Theory: Culture's Consequences or Wealth Of Nationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major changes in climate and ecology, historical events, population migration, or cultural diffusion may slowly affect culture (Triandis 1995). However, national cultures are generally thought to be stable over time , Hofstede 2001, Yeniyurt and Townsend 2003. Cross-cultural researchers have documented various dimensions of national culture.…”
Section: Theory: Culture's Consequences or Wealth Of Nationsmentioning
confidence: 99%
“…(Gelfand et al 2004) Pressure of norms, duties, and priorities of the group may discourage individuals, slowing the adoption of new products (Triandis 1995, Yeniyurt andTownsend 2003) H1: New products take off slower in countries that are high on collectivism than in countries that are low on collectivism…”
Section: Samplementioning
confidence: 99%
“…These barriers to knowledge flows have proven to be rather entrenched and persistent in society (Hofstede, 1983;Ghemawat, 2001;Ghemawat, 2003). A number of studies have shown that they actually complicate the flow of innovation knowledge across borders (Maurseth and Verspagen, 2002;Tellis et al, 2003;Yeniyurt and Townsend, 2003). Still, as O'Grady and Lane (1996) show, these distance measures are highly subjective since they can be overcome through organisational configurations, e.g., employees from abroad or with foreign experience in critical positions, and can therefore provide additional points of access.…”
Section: Accessmentioning
confidence: 99%
“…This model has been developed by Straub [11] and Veiga [32]. Straub demonstrate the exogenous social presence/ information richness factor and added it as an antecedent to the TAM, while Veiga showed the Hofstede's cultural dimension which affects the technology acceptance model.…”
Section: Introductionmentioning
confidence: 99%